Assessing the Effect of Loyalty Program Benefits in Satisfaction-Loyalty Relationship: Evidence from Malaysia - Nor Asiah Omar,; Suhaily Mohd Ramly,; Syed Shah Alam,; Muhamad Azrin Nazri (UKM Publisher, 2024)
This study aimed at examining the relationship among program benefits (utilitarian/monetary, hedonic, and symbolic), program satisfaction, and loyalty (program loyalty and store loyalty) in the retail context in Malaysia. A total of 300 questionnaires were collected via convenience sampling from program members of hypermarkets and superstores in Malaysia. A structural equation model that assessed the relationship between the proposed variables was tested using AMOS 20. The findings revealed that of the three program benefits, utilitarian benefits and symbolic benefits were statistically significant in influencing program satisfaction. In terms of loyalty, both hedonic and symbolic benefits were related to program loyalty and only hedonic benefit was positively related to store loyalty.